1998
DOI: 10.1302/0301-620x.80b2.7762
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of fractures in 15 000 adults: The influence of age and gender

Abstract: We report a prospective study of the incidence of fractures in the adult population of Edinburgh, related to age and gender. Over a two-year period, 15,293 adults, 7428 males and 7865 females, sustained a fracture, and 5208 (34.0%) required admission. Between 15 and 49 years of age, males were 2.9 times more likely to sustain a fracture than females (95% CI 2.7 to 3.1). Over the age of 60 years, females were 2.3 times more likely to sustain a fracture than males (95% CI 2.1 to 2.4). There were three main peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
297
6
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(335 citation statements)
references
References 0 publications
22
297
6
10
Order By: Relevance
“…The reduction in fracture incidence, especially in young men during the second period, was attributed almost entirely to the decline in the number of fractures seen in young motorcyclists. However, compared to our data, the incidence figures were higher (Emami et al 1996)-as in another report (Singer et al 1998). …”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The reduction in fracture incidence, especially in young men during the second period, was attributed almost entirely to the decline in the number of fractures seen in young motorcyclists. However, compared to our data, the incidence figures were higher (Emami et al 1996)-as in another report (Singer et al 1998). …”
Section: Discussioncontrasting
confidence: 54%
“…To date, rather few epidemiological studies have been undertaken to examine the incidence of this injury (Knowelden et al 1964, Bengner et al 1990, Donaldson et al 1990, Court-Brown and McBirnie 1995, Emami et al 1996, Singer et al 1998, van Staa et al 2001, and with varying results. Most of the earlier epidemiological studies were retrospective or case series from single hospitals, and prior to the present study no analyses on a nationwide basis had been undertaken.…”
mentioning
confidence: 99%
“…(78)(79)(80)(81) A comprehensive review of 6409 femoral shaft fractures in Swedish inpatients showed a bimodal age distribution of incidence in both males and females, (82) similar to that reported by Singer and colleagues. (83) The age-specific incidence rates (per 100,000) for subtrochanteric fractures increased between the 65-and 85-year categories in both males and females in Iran, (84) in the United States, (85) and in the United Kingdom. (86) Although femoral shaft fractures were more common among males than among females up to age 49, this gender difference was reversed in the 60-to 69-year age group.…”
Section: Epidemiology Of Subtrochanteric and Femoral Shaft Fracturesmentioning
confidence: 99%
“…Are younger women with osteopenia, rather than osteoporosis, at increased fracture risk? In the age group of 50-80 years, around 36% of classical osteoporotic fractures occur in those below age 65 years [10,11]. In the UK, this amounts to more than 100,000 fractures per year in women aged 50-65 years, over 9000 of which are hip fractures [10,11; www.uk2u.net].…”
Section: Hormone Replacement Therapymentioning
confidence: 99%